Physical and mechanical properties of thin high density fiberboard bonded with 1, 3-dimethylol-4, 5-dihydroxyethyleneurea (DMDHEU). Issue 7 (18th May 2020) - Mamiński, Mariusz Ł.; Trzepałka, Andrzej; Auriga, Radosław; H'Ng, Paik San; Chin, Kit Ling
ABSTRACT: 1, 3-dimethyl-4, 5-dihydroxyethyleneurea (DDHEU) and 1, 3-dimethylol-4, 5-dihydroxyethyleneurea (DMDHEU) were used as the binders in 3-mm high density fiberboard (HDF) manufacturing. The studies focus on the physical and mechanical properties of boards bonded with DDHEU or DMDHEU as a potential substitute for typically used urea-formaldehyde (UF) resins. The adhesive loads were 8% or 12%. The UF-bonded boards of same resin load were used as the controls. Applied pressing time ranged between 4 and 5 minutes. The results indicate that the use of DDHEU or DMDHEU as binders enhanced physical and mechanical properties of the boards. It was found that properly set pressing scheme and resin type allowed produce DDHEU- and DMDHEU-bonded HDF that exhibited comparable or superior performance when compared to the UF-bonded reference series and complied with European Standards. The best performing boards exhibited internal bond 1.3 MPa, modulus of elasticity 9656 MPa, modulus of rupture 56.5 MPa, thickness swelling 14% and formaldehyde release below 3.0 mg/m 2 h. Due to low reactivity of DDHEU and DMDHEU at temperatures below 160°C, the approach is effective for thin boards only.